Idiopathic scrotal calcinosis: A new case report - Hedhli, Houcem (Urol Case Rep, 2020)
Scrotal calcinosis is a rare benign pathology and its etiology is still discussed. The main complaint is mostly aesthetic. The treatment of extended forms is a one-staged excision. The aim of our study was to study clinical and anatomopathological aspects and report our surgical management of a case of diffuse scrotal calcinosis. We report a case of 24-year-old patient who consulted for painless scrotal nodules lasting for 2 years. Scrotal calcinosis diagnostic was based on clinical examination. The treatment was a one-staged scrotal excision taking all nodules and the plasty of the scrotum. The diagnosis was confirmed by a histopathological examination of surgical specimen.